The Moderating Effects of Social Media Activities on the Relationship Between Effort-Reward Imbalance and Health and Wellbeing: A Case Study of the Oil and Gas Industry in Malaysia - Kanwal, Noreen; Isha, Ahmad Shahrul Nizam (Frontiers in Public Health, 2022)
Background: Social media activities affect every aspect of human life, be it personal, social or professional. Previous studies have confirmed the role of social media in affecting health in terms of releasing stress and providing social support. Increased occupational health disorders and increased time spent on social media activities motivate us to investigate this phenomenon in the context of occupational health. Therefore, the objective of this study is to measure the effects of social media activities related to personal and social life as well as work-life on health and well-being of office employees, on their job efforts and job rewards, and in moderating the effect of effort-reward imbalance on health and well-being. Methods: Initially, to develop constructs related to social media activities, web-based structured interviews were conducted with five office employees working in the oil and gas industry for the last five years. Then, using an online questionnaire survey, data was collected from 424 office employees working in the oil and gas industry in Malaysia. Using statistical software for social science (SPSS) and Smart PLS, exploratory factor analysis and confirmatory factor analysis were conducted to identify reliability and validity (discriminant validity, convergent validity and composite validity) of the constructs. Following this, path analysis was conducted and the moderating effects were identified. Results: Social media activities related to work-life decrease health and well-being by 11% and weaken the negative effect of effort-reward-imbalance on health and well-being by 17.6% at a 1% level of significance. The results of social media activities related to personal and social life strengthen the negative effect of effort-reward imbalance on health and well-being by 12% and negatively affects health and well-being and job rewards by 13%, 55% respectively. The direct effect of effort-reward imbalance and job efforts is significantly negative on health and well-being by 59% and 10% respectively. Conclusion: It is concluded that social media activities of the office employees significantly moderate the effect of effort-reward imbalance on health and well-being and intervene in job rewards in the organizations. Hence, the effect of social media activities reduces the health and well-being of office employees.